Prospect of Stem Cell Therapy and Regenerative Medicine in Osteoporosis - Arjmand, Babak; Sarvari, Masoumeh; Alavi-Moghadam, Sepideh; Payab, Moloud; Goodarzi, Parisa; Gilany, Kambiz; Mehrdad, Neda; Larijani, Bagher (Frontiers in Endocrinology, 2020)
The field of cell therapy and regenerative medicine can hold the promise of restoring normal tissue structure and function. Additionally, the main targets of stem cell-based therapies are chronic diseases and lifelong disabilities without definite cures such as osteoporosis. Osteoporosis as one of the important causes of morbidity in older men and post-menopausal women is characterized by the reduced bone quantity or skeletal tissue atrophy that leads to an increased risk of osteoporotic fractures. The common therapeutic methods for osteoporosis only can prevent the loss of bone mass and recover the bone partially. Nevertheless, stem cell-based therapy is considered as a new approach to regenerate the bone tissue. Herein, mesenchymal stem cells as pivotal candidates for regenerative medicine purposes especially bone regeneration are the most common type of cells with anti-inflammatory, immune-privileged potential, and less ethical concerns than other types of stem cells which are investigated in osteoporosis. Based on several findings, the mesenchymal stem cell's effectiveness near to a great extent depends on their secretory function. Indeed, they can be involved in the establishment of normal bone remodeling via initiation of specific molecular signaling pathways. Accordingly, the aim herein was to review the effects of stem cell-based therapies in osteoporosis.